1987
DOI: 10.1016/0014-5793(87)80371-x
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of eicosanoids in the actions of sympathetic hepatic nerves on carbohydrate metabolism and hemodynamics in perfused rat liver

Abstract: In isolated rat liver perfused at constant pressure with Krebs-Henseleit buffer containing 5 mM glucose, 2 mM lactate, 0.2 mM pyruvate and 0.1% bovine serum albumin, perivascular nerve stimulation (20 V, 20 Hz, 2 ms) and infusion of ATP (100 PM), noradrenaline (1 PM) or arachidonic acid (100 PM) caused an increase in glucose and lactate output and a reduction of perfusion flow. The metabolic effects of nerve stimulation but not those of ATP and noradrenaline were inhibited strongly by the phospholipase AZ inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…san [ l I], endotoxins [12], heat-aggregated immunoglobulins [13], peptides of the activated complement system [14-161, platelet-activating factor [ 171, extracellular nucleotides and nucleosides [18,191, phorbol esters [20,211 and stimulation of sympathetic hepatic nerves [22]. Many of these effectors have also been shown to stimulate eicosanoid formation in Kupffer cells.…”
mentioning
confidence: 99%
“…san [ l I], endotoxins [12], heat-aggregated immunoglobulins [13], peptides of the activated complement system [14-161, platelet-activating factor [ 171, extracellular nucleotides and nucleosides [18,191, phorbol esters [20,211 and stimulation of sympathetic hepatic nerves [22]. Many of these effectors have also been shown to stimulate eicosanoid formation in Kupffer cells.…”
mentioning
confidence: 99%
“…The mechanism of nerve action is more complex than an interaction of two hormones. Probably, the nerve effects are mediated by interactions of the nerve endings of the neurons, the non-parenchymal cells and parenchymal cells [13,24]. The presynaptic site of action was excluded by the determination of the unaltered overflow of noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that inhibitors of the synthesis of prostanoids reduced the nerve-mediated effects [13]. Prostaglandins were reported to be released after nerve stimulation [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently evidence has been obtained that eicosanoids, which are synthesized only in non-parenchymal liver cells, mainly endothelial and Kupffer cells [61], might be involved as mediators and/or modulators of sympathetic nerve action on both hepatic metabolism and hemodynamics [62]. Since eicosanoid formation requires the liberation of arachidonate from endogenous phospholipids [61] by calcium-activated phospholipase A2 [63], the possibility has to be considered that intracellular calcium plays a role in the metabolic nerve action not only in the hepatocytes proper but also in the non-parenchymal liver cells.…”
Section: Calciummentioning
confidence: 99%